Journalism and New Media - John V. Pavlik (Columbia University Press, 2001)
Journalism is undergoing a fundamental transformation, perhaps the most fundamental since the rise of the penny press of the midnineteenth century. In the twilight of the twentieth century and the dawn of the twenty-first, there is emerging a new form of journalism whose distinguishing qualities include ubiquitous news, global information access, instantaneous reporting, interactivity, multimedia content, and extreme content customization. In many ways this represents a potentially better form of journalism because it can reengage an increasingly distrusting and alienated audience. At the same time, it presents many threats to the most cherished values and standards of journalism. Authenticity of content, source verification, accuracy, and truth are all suspect in a medium where anyone with a computer and a modem can become a global publisher. Although the easy answer is to point to the Internet, the reasons for the transformation of journalism are neither simple nor one-dimensional. Rather, a set of economic, regulatory, and cultural forces, driven by technological change, are converging to bring about a massive shift in the nature of journalism at the millennium